DETERMINATION OF THE PRIORITY SCALE OF FLOOD MANAGEMENT IN THE LANDAK SUB-WATERSHED - Akafi, M. Ma'ruf; Soeryamassoeka, SB; Gunarto, Danang; Nirmala, Azwa; Danial, Mochammad Meddy (Jurnal Teknik Sipil, 2023)
The Landak Sub Watershed is part of Indonesia's Kapuas River Basin, covering an area of approximately 7,921 km2 and comprising three administrative regions: Landak Regency, Kubu Raya Regency, and Pontianak City. Like other regions in Indonesia, the frequency of flood events in the Landak Sub Watershed has been increasing each year, becoming a severe problem as it has caused losses for the community. Therefore, a study is needed to provide an overview of the most suitable flood management measures to minimize floods in the Landak Sub Watershed.This article presents the research results to determine the priority scale of flood mitigation measures suitable for implementation in the Landak Sub Watershed using the Analytic Hierarchy Process (AHP). The determination of criteria, sub-criteria, and flood management alternatives is based on the results of a Focus Group Discussion (FGD) held in Ngabang City on August 30, 2022. The selected flood management alternatives combine both structural and non-structural measures. Once the hierarchy is established, a questionnaire is distributed to determine the appropriate options for flood mitigation in the Landak Sub Watershed.The study results indicate that the priority scale for flood mitigation in the Landak Sub Watershed is by revising regulations and policies. The analysis shows that the priority criterion is Law and Institutions with a weight of 0.376, the priority sub-criterion is Legislation with a weight of 0.213, and the priority alternative is the revision of regulations and policies with a weight of 0.1984. For the correction of rules and procedures to be effectively carried out, all stakeholders related to flood control in the Landak Sub Watershed must be involved.